Qiwāmah and Musyāwarah in Household: Interpretation of the Qur'an and Hadith on the Equality of Husband and Wife - Masita; Ilyas Husti; Hidayatullah Ismail (Journal of Practice Learning and Educational Development, 2026)
This research aims to explore the application of the principles of justice from the Qur'an and Hadith in the occurrence of imbalances in husband-wife relations within the context of equality. Justice is a fundamental value in Islam that encompasses various aspects of life. This study involves the analysis of the Qur'an and the Qowwam hadith to identify principles of justice that can be adapted in the context of gender in husband-wife relations in the modern era. The research method used includes a qualitative approach with primary data collection thru literature study and analysis of the Qur'an and hadith texts. Secondary data is also used to support the interpretation and application of qowwam principles in the gender context. The analysis results show that the Qur'an emphasizes the importance of justice in decision-making, resource distribution, and the imbalance in husband-wife relationships within a household. This research contributes to expanding the understanding of how the values of the Qur'an and Hadith provide solutions for the integrity of a household and prevent disputes over duties and responsibilities, which often lead to domestic violence due to the context of qawwam being interpreted as men being leaders and rulers in a household. In household life, understanding the roles and responsibilities of each husband and wife is very important. This article aims to analyze the justice of the Qur'an and Hadith in the relevance of husband and wife in the modern era in the context of qawwamah and gender.